2016
DOI: 10.1002/elsc.201600074
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and molecular modeling of a unique lipase from Staphylococcus arlettae JPBW‐1

Abstract: A three‐step purification of a unique lipase with halo‐, solvent‐, detergent‐, and thermo‐tolerance from Staphylococcus arlettae JPBW‐1 gave raise to a 27‐fold purification with a specific activity of 32.5 U/mg. The molecular weight of the purified lipase was estimated to be 45 kDa using SDS–PAGE, and its amino acid sequence was characterized using MALDI‐TOF‐MS analysis. The sequence obtained from MALDI‐TOF‐MS showed significant similarity with the capsular polysaccharide biosynthesis protein (CapD) of Staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…Several instrumental techniques for structural analysis such as X-ray crystallographies, circular dichroism, Fourier transform infrared (FTIR), electrospray ionization (ESI), and matrix-assisted laser desorption/ionization (MALDI) have been performed to elucidate the molecular structure of lipases. Three-dimensional (3D) structures of many lipases share similar α / β hydrolase fold and have the same catalytic mechanism in which active site is formed by a catalytic triad of serine (Ser), aspartatic acid (Asp)/glutamic acid (Glu), and histidine (His) [ 14 , 16 ]. Lipases also share a consensus pentapeptide sequence of Gly-X-Ser-X-Gly motif, whereby X may be any amino acid residue [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several instrumental techniques for structural analysis such as X-ray crystallographies, circular dichroism, Fourier transform infrared (FTIR), electrospray ionization (ESI), and matrix-assisted laser desorption/ionization (MALDI) have been performed to elucidate the molecular structure of lipases. Three-dimensional (3D) structures of many lipases share similar α / β hydrolase fold and have the same catalytic mechanism in which active site is formed by a catalytic triad of serine (Ser), aspartatic acid (Asp)/glutamic acid (Glu), and histidine (His) [ 14 , 16 ]. Lipases also share a consensus pentapeptide sequence of Gly-X-Ser-X-Gly motif, whereby X may be any amino acid residue [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…L2 lipase revealed that topological organization of α / β -hydrolase fold consisting of 11 β -strands, 13 α -helices, serine-113, histidine-358, and aspartate-317 with single Ca 2+ and Zn 2+ was found in this lipase molecule [ 17 ]. Recently, amino acid sequence of lipase from S. arlettae JPBW-1 was characterized using MALDI-TOF-MS analysis and comparative modelling approach was performed via ROBETTA server to postulate a structure-activity relationship of the lipase [ 16 ]. In one study, it was found that TA lipase from Cohnella sp.…”
Section: Introductionmentioning
confidence: 99%
“…Algumas dessas enzimas são estáveis em uma ampla variação de pH, normalmente, entre 4 e 9. A faixaótima de temperatura em relaçãoà atividade pode variar entre 30 e 40 • C, no entanto, algumas lipases têm mostrado níveis de estabilidade moderado em temperaturas extremas, como, por exemplo, 5 e 70 • C [20,21]. As lipases normalmente não requerem cofatores, mas cátions divalentes, tal como o cálcio, tende a estimular sua atividade.…”
Section: Propriedades E Características Das Lipasesunclassified
“…The world market for enzymes in 2014 reached 4.2 billion dollars, projected to grow at rate of 7 % per year between 2015 and 2020, and the lipase market is expected to reach 590.5 million dollars in 2020 (Chauhan et al 2016). During the last decade, lipases have been studied as a biocatalyst for the production of biodiesel, for its importance as biofuel.…”
Section: Introductionmentioning
confidence: 99%